Analisis Bibliometrik terhadap Perkembangan Topik Penelitian Standarisasi Kualitas Perpustakaan di Indonesia pada Database Scopus Tahun 2018-2023 menggunakan VOSviewer dan CitNetExplorer - Arya Wijaya Pramodha Wardhana; Rahma Sugihartati; Tamara Adriani Salim; Laksmi; Abi Rafdi Ramadhan (Perpustakaan Nasional, 2023)
In the evolving landscape of modern libraries, where the demand for service innovation and the imperative for standardized services intersect with existing gaps in their fulfilment. This research examines the development of research on library quality standardization in Indonesia from 2018 to 2023, utilizing the Scopus international scholarly publication database. Three main questions were explored: (1) The quantity of international scholarly publications on library quality standardization in Indonesia during this period; (2) The involvement of core journals in international publications on library quality standardization in Indonesia; (3) The landscape of international research publications on library quality standardization in Indonesia based on keywords. Research data were collected through Scopus searches using customized keywords and filters, and analysis was conducted using Scopus Analyze Search, VOSviewer, and CitNetExplorer. Findings indicate that the peak development of the library quality standardization topic in Indonesia was in 2022 with 16 articles, and the